PENGEMBANGAN BAHAN AJAR IPA INTEGRATIF BERBASIS PENDEKATAN KONTEKSTUAL - BUJURI, DIAN ANDESTA; BAITI, MASNUN (Universitas Islam Negeri Raden Intan Lampung, 2018)
Teaching materials used so far are less integrative and contextual in learning, so that the impact on the achievement of learning outcomes that are not optimal is not even rare for students to obtain learning outcomes below the standard set. The purpose of this research is to make contextual approach-based development of integrative science teaching material in MI Nurul Haromain Kulon Progo. The method of this research is research and development. The research steps are potential and problem, data collection, product design, design validation, design revision, product testing, product revision, and final product. The subject of this reserach is fifteen students of fourth level students. The percentage of students’s learning success from the final product trial was obtained on the affective aspect 80% satisfying, on the cognitive aspects 86.66% satisfying, and on the skill aspects 83.33% satisfying. According to the research result, the researcher concluded that contextual approach-based development of integrative science teaching material be able to create active, effective, pleasent, meaningful, and functional learning which had an impact on students' satisfied learning success.